Idiomatic Expressions and the Internet: On Current Problems of Modern Phraseology - Dobrova, Mariia (Bohemica Olomucensia, 2016)
The article examines the ``cross points'' of two elements: of Russian phraseology and a new communication space - the Internet-discourse. A study of the use of language units in the online-space allows to see their functioning and their place in the formation of the texts of the communication network and to establish the role of the Internet discourse in the emergence of idiomatic expressions and their contextual implementation.
Keywords: phraseological unit; Russian language; the Internet-discourse; language of the Internet; phraseological unit modification; stylistic use of the idioms; phraseological neologism